Registration of RTx3410 through RTx3428 Sorghum Germplasm Resistant to Sugarcane Aphid [Melanaphis sacchari (Zehntner)]. Issue 3 (26th July 2018) - Peterson, G. C.; Armstrong, J. S.; Pendleton, B. B.; Stelter, M.; Brewer, M. J.
Abstract : The sorghum [ Sorghum bicolor (L.) Moench] germplasm lines RTx3410 through RTx3428 (Reg. No. GP‐846 to GP‐864, PI 686993 to PI 687011) were developed and released by Texas A&M AgriLife Research, Lubbock, TX, in 2018. The lines are resistant to damage caused by the sugarcane aphid [ Melanaphis sacchari (Zehntner) (Hemiptera: Aphididae)] (SCA). All lines were developed by intentional plastic bag emasculation crosses and selected using the pedigree method of plant breeding. Resistance in RTx3410 through RTx3426 was identified after the SCA became a consistent pest of sorghum in the United States in 2013. To develop RTx3427 and RTx3428, crosses and selections were made in the Texas A&M AgriLife Research program at various Texas locations and resistance to the SCA in southern Africa was identified in Botswana and South Africa. Resistance in the United States was confirmed following identification of virulent SCA in 2013. All lines at seedling and adult plant stages expressed moderate to high levels of resistance to SCA. Resistance in RTx3412 to RTx3426 is derived either from Tx2783 or an early generation sib. Resistance in RTx3410, RTx3411, RTx3427, and RTx3248 is from unknown sources of resistance. The genetic relationship between the resistance gene(s) from the different sources is not known. The lines with potentially diverse sources of resistance provide the sorghum industry with a diversity of elite germplasm with resistance to SCA.